CUDOS Commonwealth Universities Database Online Service - The Association of Commonwealth Universities (London : Association of Commonwealth Universities, 2010)
Commonwealth universities yearbook', which covers senior staff, general facilities, study options and research strengths and'International awards', which collects materials on sources of funding available at undergraduate, graduate and postdoctoral level for those who wish to study abroad in a country other than their own. These two collections have been brought together to underpin CUDOS. CUDOS comprises records of: 700 university institutions, 178,000 senior academics and administrators, 35,000 departmental research interests, 23,000 study options and 950 award schemes.
System requirements: Recommended requirements: 1Gb+ RAM ; 250Mb Free space ; 2Ghz+ CPU ; 48x+ CD read speed. Minimum requirements: 512Mb RAM ; 250Mb Free space ; 2Ghz CPU ; 32x CD read speed
Keywords: Universities and colleges -- Commonwealth countries -- Directories; Research grants -- Commonwealth countries -- Directories; Scholarships -- Commonwealth countries -- Directories